Pengaruh Pengembangan Karir dan Kepuasan Kerja terhadap Kinerja Karyawan Pada PT. Korea Tomorrow & Global Kota Jambi - Devita, Reni; Emil, Muhammad; Rasdi, Rasdi; Rahmaharani, Gita (Universitas Batanghari Jambi, 2024)
The importance of human resource management to get employees withgood performance, companies must try to meet the needs of their employees. This can be done through career deveploment and employee job satisfaction. This research aims to: 1) To describe career deveploment, job satisfaction, and employee performance at PT. Korea Tomorrow & Global Jambi City; 2) To determine and analyze the influence of career deveploment and job saticfaction on employee performance at PT. Korea Tomorrow & Global Jambi City partially; 3) To determine and analyze the influence of career deveploment and job saticfaction on employee performance at PT. Korea Tomorrow & Global Jambi City simultaneously. The method used in this research is a descriptive quantitative method with research sample using the cencus method, namely the entire population is sampled as 44 peoples at PT. Korea Tomorrow & Global Jambi City. The data collected was in the form of a questionnaire using a likert scale. To answer the research objectives, researchers used descriptive analysis and multiple linear regression analysis. The results of the research show that the career deveploment variable with a t count > t table (2,428 > 2,01954) and the job satisfaction variable with a t count > t table (3,273 > 2,01954). The multiple linear regression value is Y=4,683+0,428X1+0,395X2+e and the Coefficient of Determination () value is 26,7%, while 73,e% can be explained by other variables not examined in this study. Therefore, Career Deveploment and Job Satisfaction partially have a positive and significant effect on Employee Performance at PT. Korea Tomorrow & Global Jambi City. Career Deveploment and Job Satisfaction simultaneously have a positive and significant effect on Employee Performance at PT. Korea Tomorrow & Global Jambi City.